Co-creation of human papillomavirus self-sampling delivery strategies for cervical cancer screening in rural Zimbabwe: nominal group technique - Dzobo, Mathias; Dzinamarira, Tafadzwa; Murewanhema, Grant; Chishapira, Tatenda; Dube Mandishora, Racheal S.; Fitzpatrick, Megan; Mashamba-Thompson, Tivani (Frontiers in Public Health, 2023)
Background: Human papillomavirus (HPV) self-sampling is recommended for cervical cancer screening, particularly among women who do not participate in or have access to current screening methods offered in Zimbabwe. Key stakeholder involvement is critical in co-creating acceptable delivery strategies for implementing HPV self-sampling to ensure demand and facilitate uptake by the target population. The main objective of this study was to engage key stakeholders in co-creating acceptable HPV self-sampling delivery strategies for cervical cancer screening in rural Zimbabwe.We invited key stakeholders and employed a nominal group technique (NGT) for data collection. In the first phase, the key stakeholders identified barriers to accessing and utilising current cervical cancer screening services. In the second phase, key stakeholders suggested HPV self-sampling delivery strategies. We employed the NGT to (1) identify barriers to access and utilisation of available cervical cancer screening services and (2) co-create delivery strategies for HPV self-sampling. The workshop included 8 participants (women n=4, health workers n=2 and policymakers n=2). Quantitative data was gathered by ranking ideas and qualitative data were collected from participant group discussions and analysed thematically. The results of the ranking exercise were fed back to the participants for comments.The most significant barriers to accessing and utilising current cervical cancer screening services by women were: Inadequate information and education on cervical cancer, lack of resources and funding for cervical cancer programmes, long distances to nearest health facilities, and low perceived personal risk of cervical cancer. Key stakeholders recommended enhanced education and awareness, results notification, linkage to care, community-based self-sampling, and the choice of sampling devices as potential HPV self-sampling delivery strategies.Our study demonstrated the utility of the NGT for reaching a consensus. Using the NGT, we established priority delivery strategies for HPV self-sampling cervical cancer screening.Adequate education and awareness, early results notification, choice of sampling device and community-based self-sampling were crucial to HPV self-sampling screening in rural Zimbabwe.The proposed delivery strategies can guide the development of guidelines for designing and implementing an HPV self-sampling intervention. We recommend a study to determine women's most preferred HPV self-sampling delivery strategies before implementing the intervention.